Deconstructing international politics - Dillon, Michael, 1945- (London : Routledge, 2013)
'This book is the first full length manuscript to draw on the the insights and techniques of deconstruction to analyse international relations. Influenced primarily by Derrida, it critiques the cornerstones of international relations such as modernity, the state, the subject, security and ethics and justice'--
Includes bibliographical references (p. 194-207) and index.
Keywords: International relations; International relations -- Philosophy